Impact of periodontal intervention on local inflammation, periodontitis, and HIV outcomes. (April 2016) - Valentine, J; Saladyanant, T; Ramsey, K; Blake, J; Morelli, T; Southerland, J; Quinlivan, EB; Phillips, C; Nelson, JAE; DeParis, K; Webster‐Cyriaque, J
Abstract : Objective: The aim of this study was to determine active periodontal disease status in HIV and to determine the impact of periodontal disease resolution on HIV status. Methods: In this longitudinal cohort study, 73 HIV‐positive subjects received comprehensive dental care. AAP, CDC/AAP, and BGI case definitions determined periodontal classification. Likelihood and frequency of moderate/severe periodontal disease were assessed based on demographic variables. The influence of periodontal intervention was assessed at baseline, 12, and 24 months. IL‐6 was measured in a subset of subjects. Results: Of the periodontal classifications, BGI demonstrated the highest percentage category improvement with the intervention (>50%). Moderate/severe periodontitis was positively associated with HIV regardless of race, smoking status, gender, income level, and age, and was associated with increased IL‐6. At baseline, the majority of subjects had severe periodontal disease regardless of ART status. Subjects with suppressed viral load at baseline demonstrated a significant improvement in BGI classification ( P  = 0.026), increased CD4 counts ( P  = 0.027), and decreased IL‐6 levels ( P  = 0.03). Conclusions: Periodontal inflammation was prevalent regardless of ART status. In virologically suppressed subjects, the intervention decreased periodontitis with a concomitant IL‐6 decrease and CD4 increase. These findings suggest a relationship between periodontal inflammation, oral microbial translocation, and HIV status.